The immune response to vasectomy and its relation to the HLA system. - Law, H; Bodmer, W; Mathews, J; Skegg, D (1979)
We examined 188 men who had undergone vasectomy up to 6 years previously and, for comparative purposes, 100 men who were about to undergo the operation. Blood specimens were available from a total of 283 men. Sperm antibody assays using immunofluorescence, microagglutination, and microimmobilization confirmed that the prevalance of several types of antibody is higher after vasectomy. Immobilizing and agglutinating antibodies appeared to be the most important. Trends in antibody prevalence according to the time after the operation were analyzed. Screening against lymphocytes and lymphoid lines showed that the anti-sperm activity of era was not related to anti-HLA or anti-Ia activity. Associations were examined between different types of sperm antibody, and between these antibodies and autoantibodies to other antigens. When antibody prevalence was studied in relation to HLA types, the HLA antigen A28 was found to be strongly associated with production of head agglutinating antibody (and immobilizing and immunofluorescent equatorial antibodies) after vasectomy. This is one of the first clear-cut examples of antibody production associated with the HLA system.